MANAJEMEN SISTEM PENDIDIKAN DALAM PENGAPLIKASIAN TEKNOLOGI DIGITAL TERHADAP PEMBELAJARAN DARING PADA MADRASAH TSANAWIYAH ANWARUL HASANIYYAH - Abdul Khair; Akhmad Bukhari, GT Abdul Rahman, Ihsanul Amin, Syahrani (CV. ADIBA AISHA AMIRA, 2025)
It started with the Covid-19 virus which invaded the entire world and limited all our activities, one of which was in the field of education, which required the education system to adapt to the current situation. The solution is online learning. This research aims to describe the management of the application of digital technology to online learning, the use of applications that can support online learning systems, funding issues in learning practices, procurement of equipment to carry out online learning, students' abilities in implementing online learning and subjects that are suitable for learning methods. online. The research was conducted using a descriptive and comparative quantitative approach, with a sample of 150 people (census sample). The research was conducted on students in grades 8 and 9 of Madrasah Tsanawiyah Anwarul Hasaniyyah.